Original paperAdjuvant and definitive radiation therapy for primary carcinoma of the vagina using brachytherapy and external beam radiation therapy - Platta, Christopher S.; Anderson, Bethany; Geye, Heather; Das, Rupak; Straub, Margaret; Bradley, Kristin (Journal of Contemporary Brachytherapy, 2013)
Purpose: To report the outcomes of patients receiving vaginal brachytherapy and/or external beam radiation therapy (EBRT) for primary vaginal cancer. Material and methods : Between 1983 and 2009, 63 patients received brachytherapy and/or EBRT for primary tumors of the vagina at a single tertiary center. Patient data was collected via chart review. The Kaplan-Meier method was used to calculate actuarial pelvic local control (LC), disease-free survival (DFS), overall survival (OS), and severe late toxicity rates. Acute and late toxicities were scored according to the Common Terminology Criteria for Adverse Events version 3 (CTCAE v3.0). Results: Median follow up was 44.2 months. Patients with early stage disease (stages I and II) had significantly improved 5-year OS when compared to patients with locally advanced disease (stages III and IVA) (73.3 vs. 34.4%, p = 0.032). Patients with greater than 1/3 vaginal involvement had significantly worse prognosis than patients with tumors involving 1/3 or less of the vagina, with the later having superior DFS (84.0 vs. 52.4%, p = 0.007) and LC (86.9 vs. 60.4%, p = 0.018) at 5-years. Age, histology, and brachytherapy technique did not impact treatment outcomes. The 5-year actuarial grade 3 or higher toxicity rate was 23.1% (95% CI: 10.6-35.6%). Concurrent chemotherapy had no impact on outcomes or toxicity in this analysis. Conclusions : Success of treatment for vaginal cancer depends primarily on disease stage, but other contributing factors such as extent of vaginal involvement and tumor location significantly impact outcomes. Treatment of vaginal cancer with primary radiotherapy yields acceptable results with reasonable toxicity rates. Management of this rare malignancy requires a multidisciplinary approach to appropriately optimize therapy.